Computational modeling and simulation of electro- hydrodynamic (EHD) ion-drag micropump with planar emitter and micropillar collector electrodes - Shakeel Ahmed, Kamboh; Labadin, Jane; Henry Rigit, Andrew Ragai (IOP Publishing, 2013)
Computational models can be used to simulate a prototype of electrohydrodynamic (EHD) ion-drag micropump with planar emitter and micropillar collector electrodes. In this study, a simple and inexpensive design of an ion-drag micropump was modeled and numerically simulated. A three-dimensional segment of the microchannel was simulated by using periodic boundary conditions at the inlet and outlet. The pressure and velocity distribution at the outlet and in the entire domain of the micropump was obtained numerically. The effect of the gap between the emitter and the collector electrode, width and the height of micropillar and flow channel height was analyzed for optimum pressure and output flow rate. The enhanced performance of micropump was compared with existing designs. It was found that the performance of micropump could be improved by decreasing the height of micropillar and the gap between both electrodes. The numerical results also show that a maximum pressure head of about 2350 Pa and maximum mass flow rate 0.4 g min−1 at an applied voltage 1000 V is achievable with the proposed design of micropump. These values of pressure and flow rate can meet the cryogenic cooling requirements for some specific electronic devices.